Glutamine-chitosan modified calcium phosphate nanoparticles for efficient siRNA delivery and osteogenic differentiation1. Issue 31 (21st August 2015) - Choi, Bogyu; Cui, Zhong-Kai; Kim, Soyon; Fan, Jiabing; Wu, Benjamin M.; Lee, Min
<x xml:space="preserve">Abstract</x> CaP nanoparticles coated with highly cationic, glutamine-conjugated oligochitosan (Gln-OChi) are developed for siRNA delivery to significantly enhance gene transfection and knockdown efficiency with minimal cytotoxicity. This new nanocarrier can potentially be used for gene therapy.